Deep ocean storage of heat and CO2 in the Fram Strait, Arctic Ocean during the last glacial period - Ezat, Mohamed; Rasmussen, Tine Lander; Hain, Mathis P.; Greaves, Mervyn; Rae, James W.B.; Zamelczyk, Katarzyna; Marchitto, Thomas M.; Szidat, Sönke; Skinner, Luke C. (Paleoceanography and Paleoclimatology, 2021)
The Fram Strait is the only deep gateway between the Arctic Ocean and the Nordic Seas and thus is a key area to study past changes in ocean circulation and the marine carbon cycle. Here, we study deep ocean temperature, δ18O, carbonate chemistry (i.e., carbonate ion concentration [CO32−]), and nutrient content in the Fram Strait during the late glacial (35,000–19,000 years BP) and the Holocene based on benthic foraminiferal geochemistry and carbon cycle modeling. Our results indicate a thickening of Atlantic water penetrating into the northern Nordic Seas, forming a subsurface Atlantic intermediate water layer reaching to at least ∼2,600 m water depth during most of the late glacial period. The recirculating Atlantic layer was characterized by relatively high [CO32−] and low δ13C during the late glacial, and provides evidence for a Nordic Seas source to the glacial North Atlantic intermediate water flowing at 2,000–3,000 m water depth, most likely via the Denmark Strait. In addition, we discuss evidence for enhanced terrestrial carbon input to the Nordic Seas at ∼23.5 ka. Comparing our δ13C and qualitative [CO32−] records with results of carbon cycle box modeling suggests that the total terrestrial CO2 release during this carbon input event was low, slow, or directly to the atmosphere.